Case Report: Intraoperative endoscopic treatment for the “pseudo” lumen formation of jejuno-esophageal anastomosis in laparoscopic total gastrectomy - Chen, Zhixiong; Gao, Xiaojie; Shang, Jingkun; Huang, Jieli; Zhang, Shouru (Frontiers in Oncology, 2025)
Recently, the incidence of adenocarcinoma of esophagogastric junction (AEG) is increasing in China. Laparoscopic total gastrectomy plus D2 lymph node dissection is an important treatment method for AEG of Siewert type II. In order to achieve the esophagojejunostomy, surgical techniques, no matter in open surgery or in laparoscopic one, are highly demanding. This report describes a case of surgical complication during laparoscopic total gastrectomy, in which a pseudoaneurysm developed at the gastroesophageal junction during anastomosis. The condition was successfully managed with endoscopic mucosal incision and placement of a self-expanding covered metal stent (SEMs) as a salvage intervention. The purpose of this report is to share an clinical treatment experience of similar cases, and at the same time to warn surgeon to perform esophagojejunostomy carefully.